2018
DOI: 10.14419/ijet.v7i3.14.16871
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Assessment and the Most Significant Parameters for Drinking Water Quality Using Chemometric Technique: A Case Study at Malaysia Water Treatment Plants

Abstract: The objectives of this study are to determine the most significant spatial variation of drinking water pollutant and to identify the most significant parameters in each group of physico- chemical parameters (PCPs), Inorganic parameters (IOPs), heavy metals and organic parameters (HMOPs) and pesticides parameters (PPs). The Discriminant Analysis (DA) and One- Way Analysis of variance (ANOVA) showed spatial variation on four station categories and the variance of four group parameter in water drinking quality wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…At the end of the 8th week the data of the final players after drop out was taken for analysis to find out the mean differences across groups at various times [17]- [19]. The data were analysed using SPSS version 24.0 replicated from previous researches [20]- [21].…”
Section: Discussionmentioning
confidence: 99%
“…At the end of the 8th week the data of the final players after drop out was taken for analysis to find out the mean differences across groups at various times [17]- [19]. The data were analysed using SPSS version 24.0 replicated from previous researches [20]- [21].…”
Section: Discussionmentioning
confidence: 99%
“…The data were analysed using version 24.0 of SPSS replicated from previous researches [15]- [16]. Descriptive statistics [17]- [19] and repeated measures ANOVA within and between interactions was conducted to quantify the study results.…”
Section: Discussionmentioning
confidence: 99%
“…It can be used to compress a high dimensional dataset into a lower dimensional dataset. Recent study also revealed PCA is particularly useful when data on a number of useful variables has been gathered, and it is plausible that there is some redundancy in those variables [25][26][27][28][29]. Table 1 shows the descriptive statistics of anthropometric measurement and physical fitness among 600 male participants.…”
Section: Discussionmentioning
confidence: 99%